The relationship between the sphenoid and the posterior ethmoid sinuses and the optic nerves in Turkish patients - (:unkn) unknown (INT RHINOLOGIC SOC, 2004)
The sphenoid and the posterior ethmoid sinuses are surrounded by more vital structures than any other sinus. With the widespread acceptance and expanding role of endoscopic sinus surgery, a proper understanding of the anatomy of the sphenoid and the posterior ethmoid sinuses is achieved. We reviewed 100 CT studies of the paranasal sinuses belonging to patients examined for a chronic inflammatory disease of the nasal cavity and the paranasal sinuses. ne relationship between the optic nerves and the paranasal sinuses is classified into four discrete categories. Type I with a proportion of 64% is observed to be the most often localized optic nerve. Type 2 is detected in 22% of the cases; types 3 and 4 are both 7% of the total number. A bony dehiscence was detected in 13.5% of the total cases, while it was observed in 39% of type 2 and 43% of type 3. We found a pneumatization of the anterior clinoid process in 11% of the patients. ne proportion of pneumatization of the anterior clinoid process in type 3 configurations is found out to be as high as 86%. Optic nerve dehiscence was seen with a proportion of 23% in cases of pneumatization of the anterior clinoid process. Pneumatization of the posterior nasal septum was detected in 15% of the 100 cases. When the optic nerves were evaluated in these cases, mostly the type I configuration with a proportion of 63% was observed. An extensively pneumatized sphenoid sinus was detected in 4% of the 100 cases. Five of the investigated 8 optic nerves of these 4 cases were found out to be type 3 (62.5%). No significant optic nerve variations were met in patients with pneumatization of the posterior nasal septum. Nevertheless while performing surgery, it is important to bear in mind that there may be significant optic nerve variations with pneumatization of the anterior clinoid process and extensively pneumatized sphenoid sinuses.
Keywords: sphenoid sinus; posterior ethmoid sinus; optic nerve; anterior clinoid process; bony dehiscence; COMPUTED-TOMOGRAPHY; CT